2015
DOI: 10.1007/s11606-014-3154-9
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Led Behavioral Management of Diabetes and Hypertension in Community Practices: A Randomized Trial

Abstract: BACKGROUND: Several trials have demonstrated the efficacy of nurse telephone case management for diabetes (DM) and hypertension (HTN) in academic or vertically integrated systems. Little is known about the real-world potency of these interventions. OBJECTIVE: To assess the effectiveness of nurse behavioral management of DM and HTN in community practices among patients with both diseases. DESIGN: The study was designed as a patient-level randomized controlled trial. PARTICIPANTS: Participants included adult pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 31 publications
1
45
1
12
Order By: Relevance
“…In this study, the investigators demonstrate that a practice‐based, multicomponent intervention, including monthly phone‐based health coaching delivered by local health coaches, in conjunction with home BP monitoring and practice improvement activities, improves medication adherence and produces modest reduction in BP over 2 years in rural African American and white patients with a history of uncontrolled HTN. These findings are consistent with prior investigators’ findings, but extend this work to include rural and minority patients with uncontrolled hypertension in a primary care anchored delivery model.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the investigators demonstrate that a practice‐based, multicomponent intervention, including monthly phone‐based health coaching delivered by local health coaches, in conjunction with home BP monitoring and practice improvement activities, improves medication adherence and produces modest reduction in BP over 2 years in rural African American and white patients with a history of uncontrolled HTN. These findings are consistent with prior investigators’ findings, but extend this work to include rural and minority patients with uncontrolled hypertension in a primary care anchored delivery model.…”
Section: Discussionsupporting
confidence: 91%
“…Many interventions have been tested to improve BP control in patients with HTN . The findings from randomized controlled trials (RCTs) have indicated that the use of antihypertensive drug therapy is one of the most effective ways to reduce both systolic and diastolic BP .…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, the nursing diagnoses were compared and, when there was disagreement, the two researchers debated until reaching an agreement. The data obtained were organized in a database built in the software Excel version 2016 and statistical analysis was done through the Statistical Package for the Social Sciences (SPSS), version 21 …”
Section: Methodsmentioning
confidence: 99%
“…(9) Studies addressing ND for hypertensive and diabetic individuals were found, however, with small number of participants and convenience sampling, (12) case study, (13,14) others studies addressing ND/nursing interventions for hypertensive people only (15)(16)(17) or describing the ND/nursing process for diabetics (18,19) and addressing the management of the two chronic diseases without describing the ND. (20,21) Therefore, although there has been a wide discussion about the nursing process and the management of hypertension and DM, there has also been a shortage of articles describing the profile of ND of hypertensive individuals and also diabetic users of PHC with sample size from the population of interest and with data obtained through anamnesis and physical examination of all the participants by the researchers themselves. Within this perspective, this study is of great relevance to improve the care of nurses working in PHC, as well as to corroborate or confront the existing NDs in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…1 Patients who received the intervention showed no improvement in primary endpoints of systolic blood pressure or HbA1c compared to patients in the control group. Additionally, the two groups were similar for all secondary outcomes, including diastolic blood pressure, weight, and physical activity.…”
mentioning
confidence: 91%